The distribution and behaviour of Fe, Al, Si, Mn, Cu and Ni in ombrotrophic tropical peat draining blackwater estuaries on Borneo Island - Ukotije-Ikwut, Peter R.; Steiner, Zvi; Gledhill, Martha; Müller, Moritz; Oakes, Joanne M.; Sukri, Rahayu Sukmaria; Jiang, Shan; Achterberg, Eric P. (Frontiers in Marine Science, 2023)
Tropical peat swamps are essential ecosystems, which provide numerous services, and also serve as a rich source of dissolved organic carbon (DOC), hydrogen ions and trace elements to peat draining rivers. However, not much is known about trace element export from tropical peat swamps. We investigated trace element dynamics in rivers and estuaries draining tropical peat swamps on Borneo, and examined the influence of estuarine processes as well as dissolved organic carbon (DOC) on the distribution and concentration of trace elements. Our results indicate acidic conditions (pH = 3.3) and high DOC concentration (3500 µmol L−1) at salinities <1. We observed an initial release of trace elements at low salinity (0.05